Biodistribution of technetium-99m pertechnetate after Roux-en-Y gastric bypass (Capella technique) in rats - Rêgo,Amália Cínthia Meneses do (2010)
PURPOSE: The biodistribution of sodium pertechnetate, the most used radiopharmaceutical in nuclear medicine, has not been studied in details after bariatric surgery. The objective was to investigate the effect of Roux-en-Y gastric bypass (RYGB) on biodistribution of sodium pertechnetate (Na99mTc-) in organs and tissues of rats. METHODS: Twelve rats were randomly divided into two groups of 6 animals each. The RYGB group rats were submitted to the Roux-en-Y gastric bypass and the control group rats were not operated. After 15 days, all rats were injected with 0.1mL of Na99mTc- via orbital plexus with average radioactivity of 0.66 MBq. After 30 minutes, liver, stomach, thyroid, heart, lung, kidney and femur samples were harvested, weighed and percentage of radioactivity per gram (%ATI/g) of each organ was determined by gama counter Wizard Perkin-Elmer. We applied the Student t test for statistical analysis, considering p<0.05 as significant. RESULTS: Significant reduction in mean %ATI/g was observed in the liver, stomach and femur in the RYGB group animals, compared with the control group rats (p<0.05). In other organs no significant difference in %ATI/g was observed between the two groups. CONCLUSION: This work contributes to the knowledge that the bariatric surgery RYGB modifies the pattern of biodistribution of Na99mTc-.